2018
DOI: 10.3389/fpsyg.2018.02638
|View full text |Cite
|
Sign up to set email alerts
|

Self-Compassion and Cultural Values: A Cross-Cultural Study of Self-Compassion Using a Multitrait-Multimethod (MTMM) Analytical Procedure

Abstract: Self-compassion is natural, trainable and multi-faceted human capacity. To date there has been little research into the role of culture in influencing the conceptual structure of the underlying construct, the relative importance of different facets of self-compassion, nor its relationships to cultural values. This study employed a cross-cultural design, with 4,124 participants from 11 purposively sampled datasets drawn from different countries. We aimed to assess the relevance of positive and negative items wh… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
1
1
1

Citation Types

2
48
0

Year Published

2019
2019
2024
2024

Publication Types

Select...
8
1

Relationship

1
8

Authors

Journals

citations
Cited by 60 publications
(50 citation statements)
references
References 70 publications
2
48
0
Order By: Relevance
“…This suggests once more that if one wants to assess the true nature of self-compassion by means of the SCS, it is preferable to rely on the compassionate self-responding components. A similar conclusion was reached by Montero-Marin et al (2018) who adopted a multitrait-multimethod analytical procedure analyzing the SCS data from 4120 participants in 11 samples with different cultural backgrounds. Their analysis indicated that "the positively valenced [compassionate selfresponding] items, compared with the negative [uncompassionate self-responding] ones (which suffered more from method effects), were better explained by the corresponding trait factors of self-compassion" (p. 10), which led them to propose that the assessment of self-compassion with the SCS can best be confined to the compassionate items.…”
Section: New Insights In Self-compassionsupporting
confidence: 63%
See 1 more Smart Citation
“…This suggests once more that if one wants to assess the true nature of self-compassion by means of the SCS, it is preferable to rely on the compassionate self-responding components. A similar conclusion was reached by Montero-Marin et al (2018) who adopted a multitrait-multimethod analytical procedure analyzing the SCS data from 4120 participants in 11 samples with different cultural backgrounds. Their analysis indicated that "the positively valenced [compassionate selfresponding] items, compared with the negative [uncompassionate self-responding] ones (which suffered more from method effects), were better explained by the corresponding trait factors of self-compassion" (p. 10), which led them to propose that the assessment of self-compassion with the SCS can best be confined to the compassionate items.…”
Section: New Insights In Self-compassionsupporting
confidence: 63%
“…However, as is often the case with reversed items, they can form separate factors and unintentionally introduce new dimensions and/or unwanted method variance in a measure (e.g., Wong et al 2003). A recent study has indeed shown that this also applies to the SCS (Montero-Marin et al 2018). The inclusion of the uncompassionate self-responding items is especially problematic because they are clearly in contrast with the protective nature of the self-compassion construct.…”
Section: Critique On the Scsmentioning
confidence: 99%
“…In addition to sharing some properties with mindfulness, studies based on a work-related context have shown that selfcompassion is a correlate and predictor of a range of positive mental health outcomes (e.g., Montero-Marin et al, 2018;Kotera et al, 2019b. For example, self-compassionate workers tend to have higher levels of well-being and experience less burnout and emotional exhaustion (Alkema et al, 2008;Dev et al, 2018).…”
Section: Introductionmentioning
confidence: 99%
“…In general, compassion forms a particular orientation of mind that is shaped in a motivational system orientated to certain sensitivity to suffering and a commitment to relieve suffering by recognising the universality of pain and the ability to meet that pain with equanimity 39 40. Compassion for the self (self-compassion) is this attitude focused on the self,41 and it has been found to be a key mechanism—together with mindfulness abilities—in the effectiveness of techniques such as MBSR and MBCT 42 43. Authors have hypothesised that self-compassion could be the ‘crucial attitudinal factor’ in the relationship between mindfulness and mental health 44.…”
Section: Introductionmentioning
confidence: 99%